IDENTIFIKASI FUNGSI STATUS RESPIRASI PADA PEKERJA PABRIK AKIBAT DAMPAK DARI LIMBAH PABRIK KERTAS - Nur Aini; Lilis Setyowati (Jurnal Kesehatan Mesencephalon, 2020)
Paper factory in Indonesia contributes greatly to the country's economy, especially the non-oil export sector. However, the result of industrial process waste or waste causes environmental pollution problems if it is not managed properly and has an impact on the surrounding community. The purpose of this study was to identify the respiratory status function of the impact of paper mill waste. This research is descriptive-explorative. That aims to describe variables related to respiratory problems, sociodemographic characteristics of factory workers include: age, sex, use of PPE (personal protective equipment), BMI (body mass index), respiratory function examined by Spirometry and instrument SGRQ. The population in this study were factory workers, sampling using purposive sampling. Forty-two people included in this study, conducted in July-August 2019. Respiratory function was measured using SGRQ (St George's Respiratory Questionnaire) instrument to measure the quality of life on patient respiratory function and Spirometry to measure FEV 1 / FVC (forced expiratory volume in 1 second). Results 41 (93.18%) abnormal spirometry values, mean FEV 1/FVC 65.04% (SD: 23:53), mean spirometry prediction of 77.27% (SD: 24.98). SGRQ shows a worse quality of life for factory workers. The conclusions of the study respondents had an abnormal respiratory function. Encourage factory workers to use PPE and improve their nutritional status to reduce symptoms in their respiratory problems. The community cannot leave the job even though it hurts health because the work is a source of family income so they may not leave it. Keywords: SGRQ, respiratory function, paper factory waste, Spirometry Abstrak : Pabrik kertas di Indonesia memberikan kontribusi sangat besar dalam bidang perekonomian Negara, terutama bidang ekspor non migas. Namun, limbah hasil akhir proses industri atau sampah menimbulkan masalah pencemaran lingkungan jika tidak dikelola dengan baik dan benar dan berdampak pada masyarakat sekitar. Tujuan penelitian ini adalah mengidentifikasi fungsi status respirasi akibat dampak dari limbah pabrik kertas. Desain penelitian ini adalah deskriptif eksploratif yaitu bertujuan untuk mendeskripsikan atau menggambarkan sejumlah variabel yang berkaitan dengan masalah, antara lain karakteristik sosiodemografi pekerja pabrik meliputi : usia, jenis kelamin, penggunaan APD (alat pelindung diri), BMI (body mass index), fungsi status respirasi yang diperiksa dengan spirometri dan instrumen SGRQ. Populasi dalam penelitian ini adalah pekerja pabrik, pengambilan sample dengan teknik purposive sampling, sebanyak  42 orang. Penelitian dilakukan pada bulan Juli – Agustus 2019. Fungsi status respirasi diperiksa menggunakan instrumen SGRQ (St George’s Respiratory Questionnaire untuk mengukur kualitas hidup pada fungsi pernafasan dan spirometri untuk mengukur FEV 1/FVC (forced expiratory volume in 1 second). Hasil 41 orang (93,18 %) nilai spirometri tidak normal, mean FEV 1/FVC 65.04 % (SD : 23.53), mean prediksi spirometri 77,27% (SD: 24,98). SGRQ menunjukkan kualitas hidup buruk. Kesimpulan hasil penelitian, sebagian besar responden memiliki fungsi respirasi yang tidak normal. Disarankan kepada pekerja agar menggunakan APD dan meningkatkan status gizinya sehingga bisa mengurangi gejala–gejala pada masalah pernafasan, karena pekerjaan tersebut adalah sumber income keluarga sehingga mereka tidak mungkin meninggalkannya. Kata Kunci : SGRQ, fungsi pernafasan, limbah pabrik kertas, spirometri